ANALISIS KOMPARATIF KARAKTERISTIK DEMOGRAFI DALAM MENGADOPSI SMARTPHONE DI KOTA DENPASAR - Putra, I Gusti Agung Girinatha; Warmika, Gede Ketut (E-Jurnal Manajemen, 2013)
This study analyzes the demographic characteristics in the adoption of smartphone in the city of Denpasa. Responden smartphone adoption in this study are cell phone users in the city of Denpasar, amounting to 150 people. Data analysis technique used is the chi square. The results of this study indicate that there are significant differences in the adoption of smartphones based on demographic characteristics. Keywords: Demographic, Adoption, Smartphone